Induced breeding, embryonic and larval development of Koi carp (Cyprinus carpio) in Khulna, Bangladesh - Ghosh, A.K.; Biswas, S.; Sarder, L.; Sabbir , W.; Rahaman, S.M.B. (Mesopotamian Journal of Marine Sciences, 2022)
The aim of the present study was to perform induced breeding and to observe embryonic and larval development stages in different seasons for mature male and female Koi carp, Cyprinus carpio, was done by administering the synthetic hormone ovaprim, in a single dose for males and a double dose for females at 0.4-1.0 ml/kg body weight via an intramuscular injection. Spawning occurred between 5-6 hrs after the 2nd injection in summer (April) at a temperature of 26-29 oC and 17-20 0C in winter (December). Using doses of 0.4ml/kg, 0.7ml/kg and 1.0 ml/kg of ovaprim, the fertilization rate of eggs were obtained at 42.31%, 54.55% and 61.82 % in summer and 26.92%, 38.00% and 39.23 % in winter. Hatching rates were 42.78%, 44.60% and 55.00 % in the summer season and 30.22%, 31.01% and 31.67 % in the winter season with the same doses of ovaprim. The fertilized eggs were adhesive, transparent, and spherical with diameters ranging between 0.8 mm and 1.0 mm and yellowish white in color. Due to a positive response to the hormone Ovaprim, considerable fertilization and hatching rate, short embryonic period and larval development, it is possible to conduct a successful breeding program of this species commercially